Pattern of Bacterial Pathogens and Their Susceptibility Isolated from Surgical Site Infections at Selected Referral Hospitals, Addis Ababa, Ethiopia. (30th June 2016) - Dessie, Walelign; Mulugeta, Gebru; Fentaw, Surafael; Mihret, Amete; Hassen, Mulu; Abebe, Engida
Abstract : Background . The emergence of multidrug resistant bacterial pathogens in hospitals is becoming a challenge for surgeons to treat hospital acquired infections. Objective . To determine bacterial pathogens and drug susceptibility isolated from surgical site infections at St. Paul Specialized Hospital Millennium Medical College and Yekatit 12 Referral Hospital Medical College, Addis Ababa, Ethiopia. Methods . A cross-sectional study was conducted between October 2013 and March 2014 on 107 surgical site infected patients. Wound specimens were collected using sterile cotton swab and processed as per standard operative procedures in appropriate culture media; and susceptibility testing was done using Kirby-Bauer disc diffusion technique. The data were analyzed by using SPSS version 20. Result . From a total of 107 swabs collected, 90 (84.1%) were culture positive and 104 organisms were isolated. E. coli (24 (23.1%)) was the most common organism isolated followed by multidrug resistant Acinetobacter species (23 (22.1%)). More than 58 (75%) of the Gram negative isolates showed multiple antibiotic resistance (resistance ≥ 5 drugs). Pan-antibiotic resistance was noted among 8 (34.8%) Acinetobacter species and 3 (12.5%) E. coli . This calls for abstinence from antibiotic abuse. Conclusion . Gram negative bacteria were the most important isolates accounting for 76 (73.1%). Ampicillin, amoxicillin, penicillin, cephazoline, and tetracycline showed resistance while gentamicin and ciprofloxacin were relatively effective antimicrobials.